2010
DOI: 10.1007/s00234-010-0698-1
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial hemorrhage in full-term newborns: a hospital-based cohort study

Abstract: IntroductionIn recent years, intracranial hemorrhage (ICH) with parenchymal involvement has been diagnosed more often in full-term neonates due to improved neuroimaging techniques. The aim of this study is to describe clinical and neuroimaging data in the neonatal period and relate imaging findings to outcome in a hospital-based population admitted to a level 3 neonatal intensive care unit (NICU).MethodsFrom our neuroimaging database, we retrospectively retrieved records and images of 53 term infants (1991–200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
82
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 22 publications
(33 reference statements)
9
82
1
2
Order By: Relevance
“…61 Another single center cohort study suggested similar outcomes in 53 term neonates with parenchymal hemorrhage and mortality of 25% but developmental delays in <20% and cerebral palsy in <10%. 62 Typical of all perinatal brain injury outcome studies is the limitation imposed by relatively shorter term follow-ups with most children not reaching school-age where higher order deficits manifest. NHS recurrence risk seems to be low, perhaps suggesting that one-time pathogeneses such as small vascular malformations that rupture and obliterate during transition to extrauterine life account for a significant proportion of otherwise unexplained cases.…”
Section: Neonatal Hemorrhagic Stroke (Nhs)mentioning
confidence: 99%
“…61 Another single center cohort study suggested similar outcomes in 53 term neonates with parenchymal hemorrhage and mortality of 25% but developmental delays in <20% and cerebral palsy in <10%. 62 Typical of all perinatal brain injury outcome studies is the limitation imposed by relatively shorter term follow-ups with most children not reaching school-age where higher order deficits manifest. NHS recurrence risk seems to be low, perhaps suggesting that one-time pathogeneses such as small vascular malformations that rupture and obliterate during transition to extrauterine life account for a significant proportion of otherwise unexplained cases.…”
Section: Neonatal Hemorrhagic Stroke (Nhs)mentioning
confidence: 99%
“…Although signifi cant bleeds in the posterior fossa can be picked up by CUS, as noted in our case, being and operator-dependent procedure, it has been deemed rather insensitive, particularly for retrocerebellar bleeds unless large enough to cause cerebellar displacement [13]. CT scan is therefore advised for confi rmation [14] and thus the initial management would depend on clinical judgment until then. Blauwblomme et al.…”
Section: Discussionmentioning
confidence: 83%
“…Risk factors for developing SDH in general are outlined in Table 1 [12]. Clues in the neonate can be highly variable and include any number or combination of the following; bulging fontanellae, increased occipito-frontal circumference, apnoea, bradycardia, respiratory distress, retinal haemorrhage, lethargy, fever, opisthotonus and seizures [14,15]. Volpe inferred in an article that slow-reacting or unreactive pupils due to compression of the occulomotor nerve are the most distinctive sign of posterior fossa [12].…”
Section: Discussionmentioning
confidence: 99%
“…IVH was observed in 3% of infants presenting with neonatal seizures and may be an incidental finding. 23,24 The common cause for transient metabolic disorder with MRI abnormality was hypoglycemia (88%). The typical pattern involving the occipital region and splenium of corpus callosum has been the characteristic MRI change consistently observed in infants with hypoglycemic encephalopathy.…”
Section: Discussionmentioning
confidence: 99%